The experience of support of innovative start-ups in Poland, Slovenia and Czechia: Lessons for Ukraine - Olena Kurchenko (Economic and Environmental Studies (E&ES), 2016)
The article is devoted to the problems of development small innovative enterprises - start-ups. The most successful experience of the creation and development of start-up companies in Poland, Slovenia and Czechia, including the programs of their support are investigated. It was concluded on expediency of the creation of similar mechanisms of organization and development of start-ups, taking into account Ukrainian realities.
Keywords: H25; O25; L53; 330; start-up; SMEs; innovation; program; state support; Poland; Slovenia; Czechia